2013
DOI: 10.5603/fhc.2013.0033
|View full text |Cite
|
Sign up to set email alerts
|

ACE and ACE2 expression in normal and malignant skin lesions

Abstract: Abstract:The renin-angiotensin system (RAS) is known mainly as a regulator of cardiovascular homeostasis. However, it has also been shown to mediate processes such as proliferation, apoptosis, angiogenesis, and carcinogenesis. Nonmelanoma skin cancers (NMSC) -including basal cell carcinoma (BCC) and squamous cell carcinoma (SCC) -are among the most common cancers. The aim of the present study was to determine the immunohistochemical expression of angiotensin-converting enzyme (ACE), angiotensin-converting enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…Recent experimental data suggested that ACE inhibitors and ARBs had beneficial effects on tumor progression, vascularization and metastasis and that angiotensin receptor AT 2 subtype played a role in the regulation of cell proliferation and neoplastic progression [ 27 , 28 ]. Grzegrzolka et al [ 29 ] measured the immunohistochemical expression of ACE, ACE 2 and Ki-67 antigen in archival samples of normal skin, AK and malignant skin lesions, showing a significantly higher ACE immunoreactivity in normal skin than for BCC and SCC ( p < 0.01, p < 0.0001, respectively). Additionally, ACE immunoreactivity was also significantly higher in BCC than SCC ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental data suggested that ACE inhibitors and ARBs had beneficial effects on tumor progression, vascularization and metastasis and that angiotensin receptor AT 2 subtype played a role in the regulation of cell proliferation and neoplastic progression [ 27 , 28 ]. Grzegrzolka et al [ 29 ] measured the immunohistochemical expression of ACE, ACE 2 and Ki-67 antigen in archival samples of normal skin, AK and malignant skin lesions, showing a significantly higher ACE immunoreactivity in normal skin than for BCC and SCC ( p < 0.01, p < 0.0001, respectively). Additionally, ACE immunoreactivity was also significantly higher in BCC than SCC ( p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The activity of RAS system in controlling cell proliferation and differentiation, also in case of tissues injury in the mechanism of self-renewed of damaged cells and neoangiogenesis, is reflected also in the skin, where the epidermal stem cells express the different players of this system, including ACE2 (57). Immunohistochemical evaluation of ACE2 presence in healthy and oncologic patients showed ACE2 in basal cell layer of normal epidermis and sebaceous glands and a reduction of ACE2 reactivity in patients affected by pre-malignant lesions (actinic keratosis) and non-melanoma malignant skin cancers (basal cell carcinoma and squamous cell carcinoma), suggesting an involvement in the pathogenesis of the disease (58).…”
Section: Ace2 In Human Physiology: Body Localization Expression Funmentioning
confidence: 99%
“…However, despite the wide tissue expression pattern of ACE2 and TMPRSS2, the presence of these viral entry factors in the skin has not been comprehensively assessed. Some studies have shown that ACE2 is detectable in the basal layers of epidermis, as well as in hair follicles [35,39]. Nonetheless, the presence of ACE2 in skin specimens was related to its expression by endothelial cells of cutaneous capillaries but not [12] in specific subsets of skin cells, such as keratinocytes or melanocytes.…”
Section: Expression Of Viral Entry Factors In the Skin And Possible Mmentioning
confidence: 95%